Seven deadly sins the uncomfortable truth - Boone, Dan, 1952- (Kansas City, Mo. : Beacon Hill Press of Kansas City, 2008)
This book is not a history lesson on sin or a guilt-based study on the evils of our society. It is a relevant, thought-provoking look at the seven imperfections that sin uses to tarnish and infect our lives. Written with compassion and understanding, this perceptive and challenging book will reshape your awareness of sin and remind you of a sin-free Savior who gives us the grace to become like Him.
The "S" word -- Deadly anger -- Un-deadly anger -- Envy -- Gluttony -- What's sloth? -- Sloth : back to the garden -- Sloth : coming to a church near you -- Pride -- Lust -- Greed -- Un-greed -- A life of sanctity.
Description based on print version record.
Keywords: Deadly sins; RELIGION / Christian Theology / Ethics; Electronic books